Monext: an accounting framework for federated clouds - Silva, Francisco Airton Pereira da (2013)
Cloud computing has become an established paradigm for running services on external infrastructure that dynamically allocates virtually unlimited capacity. This paradigm creates a new scenario for the deployment of applications and information technology (IT) services. In this model, complete applications and machine infrastructure are offered to users, who are charged only for the resources they consume. Thus, cloud resources are offered through service abstractions classified into three main categories: Software as a Service (SaaS), Platform as a Service (PaaS), and Infrastructure as a Service (IaaS). In IaaS, computing resources are offered as virtual machines to the end user. The aim to offer such unlimited resources necessitates distributing these virtual machines through multiple data centers. This distribution makes harder to fulfill a number of requirements including security, reliability, availability, and accounting. Accounting refers to how resources are recorded, accounted for, and charged. Even for a single cloud provider this task is hard, and it becomes more difficult for a federation of cloud computing, or federated cloud, in which a cloud provider dynamically outsources resources to other providers in response to demand variation. Thus, a cluster of clouds shares heterogeneous resources, requiring greater effort to manage and accurately account for the distributed resources. Some earlier research has addressed the development of platforms for federated clouds but without considering the accounting requirement. This dissertation presents a framework for charging IaaS with a focus on federated cloud. In order to gather information about this topic area and to generate guidelines for building the framework, we applied a systematic mapping study. This dissertation also presents an initial validation of the tool through a case study, showing evidence that the requirements generated through the mapping study were fulfilled by the framework and presenting indications of its feasibility in a real cloud service scenario